Spoštovanje etičnega načela avtonomije - temelj obravnave bolnika kot subjekta v zdravstveni negi - Košir, Alenka (Obzornik zdravstvene nege, 2004)
The article presents the ethical principle of autonomy as one of the elements of nursing care which places the patient in the centre of treatment and gives himlher the right to decide for him/herself. To be able to take the right decisions with positive consequences for his/her health and well-being, the patient has to be informed about the proceedings of nursing care and medical treatment. The respect for patient' autonomy is the starting point from which the patient proceeds from being an object to being a subject actively participating in the process of nursing care. The results of a survey on 488 nurses show how well the patients are informed with the proceedings of nursingcare and what are the reactions like when a patient declines a nursing intervention. The results reveal that according to the opinion of the majorityof nurses, the patients are sufficiently informed about the proceedings of nursing care. The majority of nurses are ready to negotiate with the patient who declines a nursing intervention, trying to convince him/her to consent with it.
Keywords: ankete; autonomy; avtonomija; Bolnik, pravice; bolniki; Ethics, Nursing; Etika zdravstvene nege; medicinska etika; Medicinska sestra-bolnik, odnosi; medicinske sestre; Nurse-Patient Relations; Patient Advocacy; pravice; Questionnaires; zdravstvena nega